Memory of stone: Heritage of the mining past - Recavarren, Ana Pía (2024)
The small town of Sierras Bayas is located in the interior of the province of Buenos Aires, Argentina. It is surrounded by four hills that constitute the physical support and, for many years, the economicsupport of the population since it is geologically composed of rocks for industrial exploitation, such as dolomite, limestone, quartzite, and granite. The history of this town has been forged by mining activity and, like the rest of the district of Olavarría, European immigration from overseas in the 19th century. Born as a mining fiscal reserve for the extractive industry in 1879, the zone was allotted to the new inhabitants, who had the opportunity to apply their mining know-how on the local rocks, settling around two large quarries and installing their respective family factories in what is nowadays the center of the city. Consequently, the mining history of Sierras Bayas can bedefined in two main periods: a proto-industrial or pre-industrial period marked by the production of lime and granite (1870 and 1917) and another moment of technological and productive complexity or industrial stage (1917-2019) corresponding to the installation of the first portland cement factory in South America...